Strategi Parenting dalam Membangun Kecintaan Anak Terhadap Lingkungan Melalui Tauladan para Nabi - Mahfudza, Amalia; Siregar, Fitria Nur Afni; Roaina, Lia; Sit, Masganti (Al Fitrah: Journal Of Early Childhood Islamic Education, 2025)
Children are a trust from Allah SWT, and it is the duty of parents, teachers, and the community to educate them as well as possible so that their potential can grow and develop optimally. Various stimulations can be provided during the growth and development process, both physically and mentally. These include introducing children to their religion, their God, good deeds as a Muslim, and getting to know their Prophet. Introducing children to the Prophet from an early age can foster a love for the Prophet through a connection with history, feelings, glory, pride, and making him a role model. In order to educate children to know and love the Prophet, parents can apply several parenting strategies based on the role models of the prophets in environmental education, the story of the Prophet Muhammad and nature conservation, the story of the Prophet Muhammad and his relationship with the environment, the story of the Prophet Moses and social awareness, and parenting strategies to build children's love for the environment. Using qualitative methods that include data collection or scientific work, this study identified various strategies implemented by parents to increase children's understanding of the importance of cleanliness. The results showed that parents utilized various parenting learning strategies, such as telling exemplary stories of the prophets and practical activities that involve children in cleaning activities. This activity not only provides hands-on experience but also helps children understand the impact of their behavior on the environment. Therefore, parenting strategies as educators, mediators, motivators, and role models are crucial in fostering children's hygiene and health habits, which will positively impact their future development.